A relational perspective on gender equality and mainstreaming. Issue 1 (1st January 2019) - Syed, Jawad; Ali, Faiza
ABSTRACT: This paper offers a relational, multilevel perspective on gender equality and mainstreaming. It argues that single-level conceptualizations of equality within organizational or legal policy domain may not fully capture the multilevel and contextual nature of gender equality and mainstreaming. Based on a review of macro-level factors (e.g. laws, policies, and culture), meso-level factors (e.g. organizational interventions), and micro-level factors (e.g. intersection of gender with social class and family status) in Pakistan, the paper develops a contextual perspective on gender mainstreaming to achieve gender equality at multiple levels.